2013
DOI: 10.1007/s10549-013-2779-4
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E receptor EP4 is a therapeutic target in breast cancer cells with stem-like properties

Abstract: The cyclooxygenase pathway is strongly implicated in breast cancer progression but the role of this pathway in the biology of breast cancer stem/progenitor cells has not been defined. Recent attention has focused on targeting the cyclooxygenase 2 (COX-2) pathway downstream of the COX-2 enzyme by blocking the activities of individual prostaglandin E (EP) receptors. Prostaglandin E receptor 4 (EP4) is widely expressed in primary invasive ductal carcinomas of the breast and antagonizing this receptor with small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 32 publications
8
60
0
1
Order By: Relevance
“…However, these studies also showed that prostaglandin E receptor, which is a downstream regulator of COX-2 enzyme, plays critical role in regulation of stemness of BC cells. 60,61 We found that ASA was unable to regulate COX-2 expression at the protein levels in Aspirin prevents breast cancer cell growth G Maity et al Figure S3). Therefore, from these collective studies, we neither strongly support the involvement of COX-2 signaling nor are able to exclude that the COX-2 protein might not play any role in the growth of BC cells or breast tumor-initiating cells or both.…”
Section: Discussionmentioning
confidence: 97%
“…However, these studies also showed that prostaglandin E receptor, which is a downstream regulator of COX-2 enzyme, plays critical role in regulation of stemness of BC cells. 60,61 We found that ASA was unable to regulate COX-2 expression at the protein levels in Aspirin prevents breast cancer cell growth G Maity et al Figure S3). Therefore, from these collective studies, we neither strongly support the involvement of COX-2 signaling nor are able to exclude that the COX-2 protein might not play any role in the growth of BC cells or breast tumor-initiating cells or both.…”
Section: Discussionmentioning
confidence: 97%
“…COX-2 is a major driver of human breast cancer progression (1)(2)(3)(4)(5), in which EP4 receptor activity plays a significant role (17,19,20). The role of COX-2 in regulating miRNAs has never been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed thrombo-embolic side effects of COX-2 inhibitors (11,12), resulting from inhibition of cardioprotective prostanoids such as PGI2 (13) may possibly be avoided by targeting EP4. We and others have shown that EP4 activity contributes to multiple mechanisms in breast cancer progression, including: inactivation of host antitumor immune cells (14,15); stimulation of tumor cell migration (16); invasiveness (16); angiogenesis (16,17); and lymphangiogenesis due to EP4-mediated upregulation of lymphangiogenic factors VEGF-C (17,18) or VEGF-D (19); induction of stem-like cell (SLC) phenotype in vitro (19,20) and in vivo (19). The role of EP4 in tumor progression has also been reported in colonic tumors (21).…”
Section: Introductionmentioning
confidence: 99%
“…39 EP receptor antagonists have been tested for their ability to suppress breast cancer metastasis. 40,41 Although the targeted modulation of T-cell function by blocking specific EP receptor signaling seems to be a promising approach, there are several limitations in the usage of EP receptor antagonist for therapy. EP receptor antagonists display many compensatory and opposing roles, such as their ability to ameliorate not only Th1 responses but also Th17 responses.…”
Section: E988460-6mentioning
confidence: 99%